Dimensions of Strategic Risk Management and Their Role in Achieving Sustainable Development: An applied study on the Ministry of Environment, Water and Agriculture in the Asir region, Kingdom of Saudi Arabia - Al-Qahtani, Atheer Mansour; Hassan, Fatimah Mohamed Mahdy (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify The Role of Strategic Risk Management with Its Dimensions (Document and Information Risks, Organizational Reputation Risks, Organizational Culture Risks, Human Resources Risks) in achieving Sustainable Development in its dimensions (Environmental Dimension, Social Dimension, Technological Dimension, Economic Dimension) in the Ministry of Environment and Water and Agriculture In Asir Region, and to identify the level of awareness of the Ministry’s employees of the importance of Strategic Risk Management in achieving the dimensions of Sustainable Development. This research followed the use of The Descriptive Analytical Method, and the researcher used the questionnaire as a tool for collecting primary information, and the study population consisted of the employees of The Ministry of Environment and Water and Agriculture in Asir Region, and their number is (1242) respondents. Where a simple random sample of (292) individuals was drawn. The SPSS and AMOS statistical package programs were used to analyse the data, as several statistical methods were adopted in analysing the research hypotheses and questions. The research concluded with several results, including that there is a statistically significant relationship for Strategic Risk Management with its dimensions in achieving Sustainable Development. The research reached a few recommendations, including: The necessity of periodic and continuous assessment of Strategic Risks, given the high risks that may arise in the ministry’s strategy in general, and work to adopt the idea of Sustainable Development in enhancing the administrative aspect of Strategic Risks, and to promote the application of the COSO framework system as a model for evaluating Strategic Risk management in the Ministry of Environment, Water and Agriculture.
Keywords: Strategic Risk Management; Environmental Dimension; Social Dimension; Technological Dimension; Economic Dimension; Sustainable Development; Ministry of Environment and Water and Agriculture